A sustainable ocean for all - Santos, Catarina; Agardi, Tundi; Allison, Edward H.; Bennett, Nathan; Blythe, Jessica; Calado, Helena; Crowder, Larry; Day, Jon; Flannery, Wesley; Gissi, Elena; Gjerde, Kristina; Gobin, Judith; et al. (Springer, 2022)
Welcome to the opening editorial of npj Ocean Sustainability. This new interdisciplinary journal aims to provide a unique forum for sharing research, critically debating issues, and advancing practical solutions to achieve ocean sustainability. The ocean and people are deeply interconnected. Thus, decision-makers require integrative, interdisciplinary, and transdisciplinary knowledge to design solutions and approaches based on the multitude of visions for what a sustainable ocean entails. For that reason, the journal recognizes the benefits of knowledge pluralism and equally welcomes research from natural and social sciences; from marine ecology to Indigenous Studies; from the legal, policy, and management sciences to medical sciences, to arts and humanities. We acknowledge the fundamental need to understand and integrate the environmental and human dimensions into ocean research and management to effectively ensure long-term sustainable ocean use and conservation. We also acknowledge that while the ocean is “one” from a biophysical standpoint, there is a “plurality” of values and relationships between humans and the ocean, emerging from multiple geographical and historical specificities that need to be accounted for.